The Acquisition of Arabic Definite and Indefinite Articles as a Second Language among Arabic Learners at King Saud University - Ahmad Nahidl Mashury Mashury; Mochammad Indra Yumanto (Journal of Arabic Language Studies and Teaching, 2022)
This research aimed to know the learner's growth of linguistic levels to identify the acquisition of Arabic definite and indefinite articles, to identify common mistakes among learners of Arabic as a second language at the Institute of Arabic Linguistics at King Saud University in Riyadh, and to know the difficulties experienced by the learners, and to provide appropriate solutions to address these difficulties. Moreover, the research methodology is the quantitative research method. It was done by designing the test as a special study tool for the selected students, then conducting the test and analyzing it, and using statistical methods to analyze the data. The research findings are; There is a steady growth of intermediate and advanced students in acquiring definition and disguise, and several common mistakes made by learners in Ma'rifat (definite article) and Nakiroh (indefinite article): the mismatch between the adjective and the described in their Ma'rifat and Nakiroh, deleting the definite article (al) from the genitive, and adding the definite article (al) in the noun added.   استهدف هذا البحث إلى معرفة النمو الملحوظ للمستويات اللغوية في اكتساب التعريف والتنكير، والتعرف على الأخطاء الشائعة لدى متعلمي العربية كلغة ثانية في معهد اللغويات العربية بجامعة الملك سعود الرياض، ومعرفة الصعوبات التي يعاني منها المتعلمون، وتقديم الحلول المناسبة لمعالجة هذه الصعوبات. ومنهجية البحث التي اعتمد عليها الباحثان هي منهج البحث الكمي حيث تم ذلك بتصميم الاختبار كأداة الدراسة الخاصة للطلاب المختارين ثم إجراء الاختبار وتحليله واستخدام الأساليب الإحصائية لتحليل البيانات. وتوصلت الدراسة إلى النتائج التالية وهي: أن هناك النمو المطرد لطلاب المستوى المتوسط والمتقدم في اكتساب التعريف والتنكير. واكتشاف عدد من الأخطاء الشائعة لدى المتعلمين في التعبير عن التعريف والتنكير؛ عدم التطابق بين الصفة والموصوف في تعريفهما أو تنكيرهما، وحذف أداة التعريف (أل) من المضاف إليه، وإضافة أداة التعريف (أل) في الاسم المضاف.